Development of a tree climbing robot - Tilakaratna, Damitha Sena Bandara; Manukid Parnichkun; Bohez, Erik L.J.; Lin, Than (Pathum Thani, Thailand : Asian Institute of Technology, 2015)
This report describes the research, mechanical analysis, design methodology, and testing procedures that were used to design and build a tree-climbing robot. The primary goal was to design and build a robot that could successfully climb a tree. After researching existing climbing robot designs, a robot prototype was built using concepts from the existing designs. The prototype was then tested to determine the effectiveness of the design. The prototype proved to be successful, being capable of gripping a tree and climb up the tree. The following report details a review of robots that have successfully climbed trees my considerations when developing a tree climbing robot design, the preliminary robot design, the final robot design, mechanical analysis, programming structure, and the results that were achieved by the robot
A capstone project report submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Engineering Mechatronics Engineering, School of Engineering and Technology
Capstone Project (B. Sc.) - Asian Institute of Technology, 2015
Keywords: Robotics; Mobile robots